Heavy Quark Physics - Manohar, Aneesh V. (Cambridge University Press, 2000)
Understanding the physics of heavy quarks gives physicists a unique opportunity to test the predictions of quantum chromodynamics and the Standard Model. This introductory text begins with a review of the Standard Model, followed by the basics of heavy quark spin-flavor symmetry and its application to the classification of states, decays and fragmentation. Heavy quark effective theory is then developed and applied to the study of hadron masses, form factors, and inclusive decay rates. The authors also discuss the application of chiral perturbation theory to heavy hadrons. Written by two world leading experts, the presentation is clear and original, with problems provided at the end of each chapter. This lucid volume is an ideal introduction to the physics of heavy quarks for graduate students and an authoritative reference for more experienced researchers.